Three new species of Gnosonesima Reisinger, 1926 (Platyhelminthes: Gnosonesimida) from the subtropical Western Atlantic - Diez, Yander L. (Zootaxa, 2026)
Three new species of Gnosonesima from the eastern coast of Florida, United States, are described herein. This discovery provides new insights into one of the least-studied genus of Platyhelminthes Rhabditophora, which until now comprised only six known species. The new taxa, G. laumeri sp. nov., G. smithi sp. nov., and G. spinifera sp. nov., are primarily distinguished by the sclerotised armature of the male copulatory organ. Additional traits, including the presence or absence of eyes and pigmentation, and the structure of the female system further support their delimitation.